Editorial (Jonathan Edwards studies, 2019)
We are pleased to present the Fall 2019 issue of Jonathan Edwards Studies. It is the continuing mission of this journal to present all aspects of Edwards Studies, and more, to encourage inquiry and engagement of Edwards and his context.